THERAPIES FOR GASTRITIS PAIN - Fuji Rahmawati (Conferences of Medical Sciences Dies Natalis, 2020)
Gastritis is one of the diseases of the digestive system that most people suffer from. In 2012, the World Health Organization (WHO) recorded that the incidence of gastritis in indonesia reached 40.8%. Symptoms that commonly occur in people with gastritis are discomfort in the stomach, heartburn, bloating, headaches, nausea and vomiting which can interfere with daily activities. Gastritis can be treated pharmacologically and nonpharmacologically. There are several non-pharmacological therapies that can be used to reduce these symptoms. This article aims to discuss various therapies to treat gastritis pain. The method used is literature study. The results of the discussion concluded that there are several therapies that can be done at home independently for patients and families in dealing with gastritis pain are deep breath relaxation techniques, progressive muscle relaxation techniques, warm compresses, and herbal therapies such as turmeric, red ginger and honey.